Technological pathways for cost-effective steel decarbonization - Xinyi Wu; Jing Meng; Xi Liang; Laixiang Sun; D’Maris Coffman; Andreas Kontoleon; Dabo Guan (Nature, 2025)
Abstract The iron and steel sector is central to national net-zero efforts but remains hard to abate 1,2 . Existing decarbonization roadmaps fail to guide technology choices for individual plants, given their heterogeneity and economic constraints 3–5 . Here, by integrating two global plant-level datasets and forecasted technology costs, we develop a model to identify the least-cost technology pathway for each plant worldwide in alignment with national carbon-neutrality targets. In the short term (pre-2030), energy efficiency improvements and scrap reuse are the cheapest decarbonization strategies, reducing cumulative global carbon dioxide (CO 2 ) emissions by 7.8 Gt and 7.2 Gt at average costs of –US$8.5 tCO 2 −1 and US$0.3 tCO 2 −1 , respectively. In the long term (after 2030), smelt reduction with carbon capture is expected to become technically mature and economically viable, achieving approximately 6.0 Gt of CO 2 reductions at costs of US$7–15 tCO 2 −1 in Chinese plants and US$26–75 tCO 2 −1 in plants across Japan, Korea and Europe. After 2040, green-hydrogen-based steelmaking is estimated to contribute an additional 0.3 Gt of CO 2 abatement in European plants at costs of US$27–44 tCO 2 −1 . This study tailors plant-specific least-cost technology pathways that reconcile stakeholders’ economic interests with climate objectives, enabling actionable decarbonization strategies and supporting global net-zero targets.